2019
DOI: 10.17159/2413-3221/2019/v47n1a488
|View full text |Cite
|
Sign up to set email alerts
|

Capacity development for scaling up Climate-Smart Agriculture (CSA) innovations: agricultural extension's role in mitigating climate change effects in Gqumashe community, Eastern Cape, South Africa

Abstract: This study aimed at ascertaining what role agricultural extension plays in mitigating the effects of climate change and variability using farmers' perceptions in Gqumashe village, Raymond Mhlaba Local Municipality, Eastern Cape, South Africa. The survey research design was adopted for the study, and data for the study were collected from 50 respondents using a convenience sampling method in the study area. Data was analysed using SPSS and descriptive statistics (means, percentages and graphs) were produced. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…National agricultural extension program needs to ensure adequate broadcast and transmission of research results about climate change to ensure that farmers become aware and adequately equipped to ameliorate the negative effects of climate change. This could assist farmers in identifying and capitalizing on strategies to cope with the variability of climate (Maka, et al, 2019). Also, extension system in Nigeria should be repositioned to aid the coping strategies of its clientele after incidences of climate change disaster by linking the farmers to sources of relief and assist in attracting agencies that will promote the rebuilding of farmer's sources of livelihood (Izuogu et al, 2015).…”
Section: Repositioning the National Agricultural Extension System Towards Building Climate Change Resiliencementioning
confidence: 99%
“…National agricultural extension program needs to ensure adequate broadcast and transmission of research results about climate change to ensure that farmers become aware and adequately equipped to ameliorate the negative effects of climate change. This could assist farmers in identifying and capitalizing on strategies to cope with the variability of climate (Maka, et al, 2019). Also, extension system in Nigeria should be repositioned to aid the coping strategies of its clientele after incidences of climate change disaster by linking the farmers to sources of relief and assist in attracting agencies that will promote the rebuilding of farmer's sources of livelihood (Izuogu et al, 2015).…”
Section: Repositioning the National Agricultural Extension System Towards Building Climate Change Resiliencementioning
confidence: 99%
“…This finding is inconsistent with some literatures, which suggest that women's contribution to farm production in many developing countries, particularly in sub-Saharan countries, is higher [40]. However, Maka et al [39] say that the reason for this kind of finding is because of the gender-related economic roles of rural communities in the Eastern Cape, where men are known to engage in farming, while women engage in petty trading. Furthermore, almost three-quarter (74%) of farmers in the study area earn an annual income of R20000 (R1667/month), showing the poverty level of study area, when compared to the current R3500 minimum wage in South Africa [41].…”
Section: A Socioeconomic Background Of the Studymentioning
confidence: 57%
“…Although age as a factor in agricultural development is dual and difficult to decide, this result is however consistent with several studies [34], [35], [36], [37], [38], which found that age rather encouraged adoption instead of acting as a drawback. Inadequate education is largely a general problem in the rural areas of the Eastern Cape, as sometimes up to 20% farmers' population still do not have formal education, and only few exceed Grade 12 level of education [39], [38]. Over and above the impact of other socioeconomic variables in agricultural development, education and poverty play significant roles.…”
Section: A Socioeconomic Background Of the Studymentioning
confidence: 99%
“…The technological advances in agriculture applied through research on smallholder agriculture guide policy and decision-making on formulating coherent and strategic policies towards resilience and attainment of Sustainable Development Goals (SDGs). According to Maka et al [10], smallholder farmers in South Africa have adopted several strategies, such as introducing diverse crop varieties, introducing new crop cultivars, changing the time of farmer operations, crop rotation, promoting crop diversification, promoting climate change awareness, using different planting dates, and educating farmers about climate change.…”
Section: Introductionmentioning
confidence: 99%